Regulation of Nuclear Factor-KappaB (NF-κB) signaling pathway by non-coding RNAs in cancer: Inhibiting or promoting carcinogenesis? - Mirzaei, Sepideh; Zarrabi, Ali; Hashemi, Farid; Zabolian, Amirhossein; Saleki, Hossein; Ranjbar, Adnan; Seyed Saleh, Seyed Hesam; Bagherian, Morteza; Sharifzadeh, Seyed omid; Hushmandi, Kiavash; Liskova, Alena; Kubatka, Peter; et al. (Cancer letters, 2021)
The nuclear factor-kappaB (NF-κB) signaling pathway is considered as a potential therapeutic target in cancer therapy. It has been well established that transcription factor NF-κB is involved in regulating physiological and pathological events including inflammation, immune response and differentiation. Increasing evidences suggest that deregulated NF-κB signaling can enhance cancer cell proliferation, metastasis and also mediate radio-as well as chemo-resistance. On the contrary, non-coding RNAs (ncRNAs) have been found to modulate NF-κB signaling pathway under different settings. MicroRNAs (miRNAs) can dually inhibit/induce NF-κB signaling thereby affecting the growth and migration of cancer cells. Furthermore, the response of cancer cells to radiotherapy and chemotherapy may also be regulated by miRNAs. Regulation of NF-κB by miRNAs may be mediated via binding to 3/-UTR region. Interestingly, anti-tumor compounds can increase the expression of tumor-suppressor miRNAs in inhibiting NF-κB activation and the progression of cancers. Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) can also effectively modulate NF-κB signaling thus affecting tumorigenesis. It is noteworthy that several studies have demonstrated that lncRNAs and circRNAs can affect miRNAs in targeting NF-κB activation. They can act as competing endogenous RNA (ceRNA) thereby reducing miRNA expression to induce NF-κB activation that can in turn promote cancer progression and malignancy. •NF-ĸB acts as a potential regulator of inflammation and is abnormal expressed in tumor cells.•Long non-coding RNAs can regulate NF-ĸB signalling by diverse mechanisms in cancer progression/inhibition.•MicroRNAs can bind to 3/-UTR of NF-ĸB to modulate its activation, and thereby affecting tumorigenesis.•Long non-coding RNAs can regulate miRNA expression that may act as upstream mediators of NF-ĸB.